2020
DOI: 10.1007/s00296-020-04529-0
|View full text |Cite|
|
Sign up to set email alerts
|

Serum immunoglobulin G4 in Sjögren’s syndrome: a pilot study

Abstract: Immunoglobulin IgG4 plays a role in the pathogenesis of the Mikulicz disease previously considered a form of primary Sjögren's syndrome (pSS). We investigated serum levels of IgG4, total IgG, C3, and C4 serum complementary components in patients suspected of Sjögren's syndrome. Basic laboratory and immunological tests, including IgG4 and IgG concentration, were performed on 20 healthy and 68 suspected of pSS individuals. We distinguished: group I: 48 pSS patients; group II (sicca): 20 patients with dryness wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…( 68 ) noted that this group had some features of IgG4-dependent disease. Another study shows a decrease in serum IgG4 concentrations in pSS patients, especially in those with high immune activity and C4 hypocomplementemia ( 69 ).…”
Section: Other Rheumatic Diseases and Igg4mentioning
confidence: 99%
See 1 more Smart Citation
“…( 68 ) noted that this group had some features of IgG4-dependent disease. Another study shows a decrease in serum IgG4 concentrations in pSS patients, especially in those with high immune activity and C4 hypocomplementemia ( 69 ).…”
Section: Other Rheumatic Diseases and Igg4mentioning
confidence: 99%
“…Maślińska et al. reported ( 69 ) the lowering of serum concentration of IgG4 below the established normal range in patients with pSS and suggested that it may be also a marker of this autoimmune disease. It was pointed out that C4 hypocomplementemia found in a significant number of pSS patients may have an impact on the reduction of IgG4 concentration and is also an indicator of disease activity taken into account in the ESSDAI assessment ( 88 ).…”
Section: Malignancies and Igg4mentioning
confidence: 99%
“…MuSK-MG First Ig-like domain in MuSK Prevent Lrp4 from binding MuSK and MuSK phosphorylation [22] Goodpasture syndrome Type IV collagen N.A [23] Iglon-5 TTP Spacer domain of ADAMTS13 Association with relapse [24] CIDP CNTN1 Block interaction of neurofascin 155 with CNTN1 [25] Transverse band loss and paranodal loop detachment Primary membranous nephropathy Neutral endopeptidase Renal involvement [26] Variable degrees of fibrosis SS SS-A Correlation with infiltrations in minor salivary glands [27] SS-B Abbreviations: ADAMTS13, disintegrin and metalloproteinase with thrombospondin motifs 13; CIPD, chronic inflammatory demyelinated polyradiculoneuropathy; CNTN1, contactin 1; MuSK-MG, muscle-specific kinase myasthenia gravis; N.A, not-assessed; SS, Sjögren's syndrome; TTP, thrombotic thrombocytopenic purpura.…”
Section: Type Of Disease Antigen Diagnostic/prognostic Value Referencesmentioning
confidence: 99%
“…A recent investigation has demonstrated a reduction in serum IgG4 levels among individuals with SS, particularly those exhibiting elevated immune activity and C4 hypocomplementemia. [27] 4 (BCR) and toll-like receptors (TLRs). [45] Upon TLR stimulation, BCR identifies distinct antigens that contain RNA and/or DNA, leading to the production of protein polypeptides and subsequent activation of B cells.…”
Section: Type Of Disease Antigen Diagnostic/prognostic Value Referencesmentioning
confidence: 99%
See 1 more Smart Citation